Preclinical Evaluation of the HDAC Inhibitor Chidamide in Transformed Follicular Lymphoma - Zhong, Mengya; Tan, Jinshui; Pan, Guangchao; Jiang, Yuelong; Zhou, Hui; Lai, Qian; Chen, Qinwei; Fan, Liyuan; Deng, Manman; Xu, Bing; Zha, Jie (Frontiers in Oncology, 2021)
The key factors leading to transformed follicular lymphoma (t-FL) include the aberrations of epigenetic modifiers as early and driving events, especially mutations in the gene encoding for histone acetyltransferase. Therefore, reversal of this phenomenon by histone deacetylase (HDAC) inhibitors is essential for the development of new treatment strategies in t-FL. Several t-FL cell lines were treated with various doses of chidamide and subjected to cell proliferation, apoptosis and cell cycle analyses with CCK-8 assay, Annexin V/PI assay and flow cytometry, respectively. Chidamide dose-dependently inhibited cell proliferation, caused G0/G1 cycle arrest and triggered apoptosis in t-FL cells. In addition, the effects of chidamide on tumor growth were evaluated in vivo in xenograft models. RNA-seq analysis revealed gene expression alterations involving the PI3K-AKT signaling pathway might account for the mechanism underlying the antitumor activity of chidamide as a single agent in t-FL. These findings provide a basis for further clinical exploration of chidamide as a promising treatment for FL.